Recognition and assessment of sinkholes as geosites: lessons from the Island of Gozo (Malta) - Coratza, Paola; Galve, Jorge Pedro; Soldati, Mauro; Tonelli, Chiara (Wydział Nauk Geograficznych i Geologicznych UAM, 2012)
There is a wide literature on sinkhole or doline classification, formation and evolution. However, despite the fact that they are often characterised by spectacular morphological features, sinkholes are not normally described as geological resources which might be valuable for the society and worth of being promoted for their geomorphological importance. A series of sinkholes have been investigated in the Island of Gozo (Malta), some of which of notable size and high aesthetic interest. These sinkholes have been assessed applying a methodology which has been specifically set up with the aim of verifying whether any of them could be considered as geosites according to their scientific, additional (ecological, aesthetic, cultural) and use values. The paper shows the geosite assessment procedure and discusses its outputs, according to which 6 out of the 17 investigated sinkholes can be considered as geosites of geomorphological interest (geomorphosites). Finally, issues related to their enhancement and fruition are taken into account in the frame of potential geotourism strategies.
Keywords: karst,; sinkhole; geosite; geomorphosite; Malta; Gozo